Avaliação de formação de hidroxiapatita em compósitos de uma planta da espécie Equisetum - DE CARVALHO, Vinicius Veríssimo; DA COSTA E SILVA, Rosangela Maria Ferreira; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2025)
-